2014
DOI: 10.5430/ijhe.v2n2p151
|View full text |Cite
|
Sign up to set email alerts
|

Entitlement Attitudes Predict Students’ Poor Performance in Challenging Academic Conditions

Abstract: Excessive entitlement -an exaggerated or unrealistic belief about what one deserves -has been associated with a variety of maladaptive behaviors, including a decline in motivation and effort. In the context of tertiary education, we reasoned that if students expend less effort to obtain positive outcomes to which they feel entitled, this should have negative implications for academic performance. We tested this hypothesis in a naturalistic experiment in a large course, in which students' self-reported entitlem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…College students are allegedly becoming increasingly self-important [ 1 ], narcissistic [ 2 , 3 ] and entitled [ 4 ], qualities that tax faculty patience [ 5 , 6 ] and raise questions about the tolerance of such traits among students’ future employers [ 7 ]. Excoriation of the “Me Generation” [ 8 , 9 ] includes reports of students pressuring faculty to succumb to relaxed academic standards as well as students’ consumer/customer-oriented mentality [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Despite contrasting data that show low levels of college student entitlement (e.g., [ 18 ]), media outlets have decried the entitled mentality of millennials responsible for “a changed relationship between the schools and the schooled [in] one of the most striking transformations in higher education over the last quarter-century” in which “[s]tudents get the message that they call the shots” ([ 19 ], para 5 and 15).…”
Section: Introductionmentioning
confidence: 99%
“…College students are allegedly becoming increasingly self-important [ 1 ], narcissistic [ 2 , 3 ] and entitled [ 4 ], qualities that tax faculty patience [ 5 , 6 ] and raise questions about the tolerance of such traits among students’ future employers [ 7 ]. Excoriation of the “Me Generation” [ 8 , 9 ] includes reports of students pressuring faculty to succumb to relaxed academic standards as well as students’ consumer/customer-oriented mentality [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Despite contrasting data that show low levels of college student entitlement (e.g., [ 18 ]), media outlets have decried the entitled mentality of millennials responsible for “a changed relationship between the schools and the schooled [in] one of the most striking transformations in higher education over the last quarter-century” in which “[s]tudents get the message that they call the shots” ([ 19 ], para 5 and 15).…”
Section: Introductionmentioning
confidence: 99%
“…Although conceptualizations of the construct vary, expectations for reward absent from achievement, responsibility avoidance, and a consumerism approach to education appear to be consistent components of AE. Unreasonable expectations associated with excessive entitlement can lead to maladaptive behaviors, such as decreased work performance, productivity, and personal responsibility [3] and has the potential to negatively alter the university environment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Exploring the relationship between AE and academic attitudes has revealed that AE is related to performance goal orientation [8,11,14] and grade orientation [15]. Past research has suggested that AE is related to negative academic outcomes such as higher levels of academic stress [16] and frustration [3] and it has shown to predict counterproductive research participant behavior, such as unexcused absence and careless survey responding [17].…”
Section: Introductionmentioning
confidence: 99%
“…Since academic entitlement might result in various psychological and educational problems, the need for having a sound grasp of academic entitlement construct has recently led researchers to validate the academic entitlement construct and develop instruments like those mentioned above. These studies and initiatives about academic entitlement have been appreciated, but much more studies are still required (Anderson, Halberstadt, & Aitken, 2013;Jackson, Singleton-Jackson, & Frey, 2011). This is also the case for the studies in Turkey, because academic entitlement has not been taken into account systematically in Turkey, yet.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, observed in many regions around the world, is a significant problem in Turkey as well. The problem of academic entitlement is stated as professors' complaints about students' impudent demanding behaviors and attitudes (Anderson et al, 2013). In Turkey, academics' personal stories comprise mostly students' inconvenient and disturbing attitudes and behaviors in recent years.…”
Section: Introductionmentioning
confidence: 99%